A multicenter, randomized, observation-controlled clinical trial to evaluate the efficacy and safety of thymalfasin adjuvant therapy in patients with HBV-related HCC after curative resection – first announcement of the protocol. (July 2015) - Qiu, Shuang-Jian; Zhou, Zhong-Guo; Shen, Feng; Li, Ai-Jun; Chen, Min-Shan; Ying, Min-Gang; Chen, Zhong; Zhang, Yi-Xin; Sun, Hui-Chuan; Fan, Jia
<x xml:space="preserve">Abstract</x> Hepatocellular carcinoma (HCC), the third leading cause of cancer-related death worldwide, is a disease of immune microenvironment. Chronic Hepatitis B virus (HBV) infection, also an immune-related disease, is the major etiological factor for HCC especially in Asia. As an immune regulator, which has pleiotropic activities on T cells, nature killer cells and dendritic cells and so on, the efficacy of thymalfasin on HCC patients has been proven by several pilot studies as an adjuvant therapy. Combination of thymalfasin significantly improved survival and prolonged the time to tumor recurrence in patients who received transcatheter arterial chemoembolization after tumor resection. An improvement in patients' immunity has also been demonstrated. However, there is no large-scale randomized controlled study so far in resectable HCC patients. To confirm the role of thymalfasin adjuvant therapy in patients with HBV-related HCC after curative resection, a large-scale multicenter randomized controlled trial has been planned in China to investigate the effect of thymalfasin (1.6 mg twice a week for 12 months) on 2-year recurrence-free survival rate and tumor immune microenvironment. Here is the first announcement of the study protocol (ClinialTrials.gov Identifier: NCT02281266).